REFLEKSJE NA TEMAT USTROJU PRACY - Piotrowski, Włodzimierz (Wydział Prawa i Administracji UAM, 2002)
Poland’s experience from 20 years ago shows that the labour system not only is determined by the prevailing economic, social and political system, but also conversely, any changes within it affect the global system. It is therefore recommendable to take more interest in labour system in the area of labour law study and social policy. The notion of labour law system, although already known in the beginnings o f the 20th c. and currently applied in the social study by the Catholic Church, tends to be understood in a variety of ways. Therefore, the author proposes two definitions of the term, one narrower denoting the work relations within a company and one broader denoting also collective work relations and their axiological assumptions on all levels as well as the relations serving them. First, the author delineates the changes in the labour system in Poland since 1918, focusing upon the labour world’s struggle for the recognition of employee’s status as fi subject in the labour process both under socialist realism and now, until trade unions accepted the social partnership principle as the basic principle fundamental for the labour system, and on to the present time when trade unions have lost their influence and significance. The author then proposes to give all work crews the right to elect organs representing them, authorized to cooperate with the employer on matters related with the employees; the author also suggests that employers’ organisations should be given the same conditions of representing their interests as those granted to trade unions. The two above proposed solutions must be applied because the Constitution of the Republic of Poland recognizes the social partnership principle as fundamental for the social and economic system, which can only be sound and effective if the two above postulates are fulfilled.
SOME REMARKS UPON LABOUR SYSTEM